The late precambrian K-alkaline magmatism in the Ribeira Fold Belt: a case study of the Piracaia Pluton, State of São Paulo, SE Brazil, and its potential mineralization (Cu, Zn, Gd) - Wernick, E.; Menezes, A. D. (Elsevier B.V., 2001)
The Pluriserial Ribeira Magmatic System-590 of the Late Precambrian Ribeira Fold Belt comprises seven groups of high-K rocks of crustal or mantle origin with ages ranging between 620 and 570 Ma. One of these groups is represented by transalkaline suites akin to appinitic lamprophyres. The suites assemble one or more of following lithologies: (+/- quartz) gabbros and monzogabbros, (+/- quartz) diorites and monzodiorites, (+/- quartz) monzonites and syenites in addition to rare granites. All these rocks occur together in the Piracaia pluton, State of São Paulo. The mineralogy of the Piracaia suite comprises variable amounts of plagioclase (An 60-10), alkali-feldspars (orthoclase, microcline, albite), ortho- (Fe-hypersthene) and clinopyroxenes (augite), amphiboles (hornblende and rare late Fe-hastingsite), abundant biotite, quartz, opaques, sphene, allanite and zircon. Several magmatic pulses constructed the pluton. The Piracaia magma bulk trend evolved initially along the silica-undersaturation plane with simultaneous fractionation of accessory, mafic and felsic minerals. These are segregated in feldspar-rich cumulates. In the late stage, the evolutionary trend followed two distinct paths: one along the or-ab thermal barrier with the crystallization of syenites; the second one along the thermal valley in the or-ab-qz subsystem, producing quartz-syenites and granites. The source of the Piracaia magma was a 'vein-plus-wall-rock-system '. Together the pulses reflect increasing and decreasing participation of peridotites and mica pyroxenites, respectively, in the magmatogenic process. The magmatic pulses were stored in magma chambers, several drained by deep faults or fractures, which were successively reactivated and recharged. Each new pulse underwent mixing with earlier residual magma, followed by fractionation. During ascent through the hot and thickened post-collisional crust, the magma pulses underwent minor compositional changes by crustal contamination. The concentration of valuable elements (Cu, Zn, Gd) in the Piracaia pluton occurred during two phases of the magmatic evolution. Cu and Zn were enriched in cumulates and Gd was concentrated in residual quartz-syenitic veins. Due to their homogeneous dark colour and texture, the monzodiorites are exploited both for polished dimension stones and supports for sensitive scientific instruments. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: Ribeira Fold Belt; K-magmatism; geochemistry; petrology; economic aspects